Ecofriendly Management of Mustard Aphid Lipaphis erysimi (Kalt), on Rapeseed in Gokuleshwor, Baitadi - Adhikari, S; Lamichhane, M.; Sapkota, P.; Parajuli, S.; Singh, N. B.; Ghimire, D. (Journal of Agriculture and Environment, 2019)
Available with full text.